Edukasi Gizi Seimbang Bagi Peserta Prolanis Diabetes Puskesmas Kecamatan Taman Sari Jakarta Barat - Corazon Hanna Dumaria; Ratih Puspitaningtyas Purbaningrum; Rosmida M Marbun; Miftahul Fauziah; Aruni Aruan (CV. Multi Kreasi Media, 2026)
The risk of type 2 diabetes mellitus increases linearly with higher Body Mass Index (BMI) and obesity status. However, many pre-elderly individuals with diabetes continue to consume high-risk foods such as those high in sugar, saturated fat, salt, and processed products as part of their daily diet. This worsens blood glucose control in diabetic patients and increases the risk of complications. This study aims to improve the knowledge of diabetes Prolanis participants in the working area of Puskesmas Taman Sari, West Jakarta, regarding balanced nutrition for the elderly. The methods used were lectures and interactive discussions. This activity involved 39 diabetes Prolanis participants. The results showed an increase in knowledge about balanced nutrition from 64% to 82% after the education session. These findings are consistent with previous studies highlighting the importance of knowledge about balanced nutrition among the elderly. Therefore, this balanced nutrition education is expected to enhance awareness and understanding among participants regarding the importance of choosing nutritious and safe foods for better health.